Head-tail disparity in irrigation management in Sri Lanka: A review of empirical evidence - L.G.D.S., Yapa; Ruslan Rainis,; Anisah Lee Abdullah,; G.P.T.S, Hemakumara (Penerbit Universiti Kebangsaan Malaysia, 2020)
Participatory Irrigation Management (PIM) was introduced in the 1990s as a problem-solving mechanism for addressing poor irrigation system performance in many agricultural areas of the world. However, there is some uncertainty as to whether this policy has achieved successful overall irrigation scheme performance in those places where it has been implemented. The emergence of head-tail differences in the water supply along the canal network has frequently resulted in irrigation system failure, causing this issue to become a subject of heated debate among scholars. Sri Lanka is one of the countries that adopted the PIM policy, where it was implemented in 1992. Therefore, this provides the opportunity to find out if head-tail disparity exists in the irrigation schemes of Sri Lanka too, as in other countries. For that reason, this article conducts a review to assess whether a head-tail difference is present or not in Sri Lanka, by determining if the problems and challenges faced by the tail-end farmers are significantly greater compared to those of the farmers in the head reaches. Of the 32 empirical studies on irrigation management done in Sri Lanka, the results of 10 studies suggest a head-tail asymmetry from the socio-economic and technical perspective. This paper identifies the knowledge gap and then provides insights that would help to overcome the existing problems and challenges of head-tail disparity in irrigation management in Sri Lanka.